Case report: A rare immune-related adverse effect: hepatic cavernous hemangioma induced by camrelizumab - Zhang, Chuantao; Wang, Guanqun; Liu, Ning; Li, Tianjun; Zhu, Jingjuan; Hou, Helei (Frontiers in Immunology, 2024)
Background: Camrelizumab, a programmed death 1 (PD-1) inhibiting antibody, has demonstrated efficacy in various malignancies and received approval in multiple countries. Despite its therapeutic benefits, camrelizumab is associated with a unique spectrum of immune-related adverse effects (irAEs), predominantly reactive cutaneous capillary endothelial proliferation (RCCEP). However, visceral manifestations of such endothelial proliferations, particularly hepatic cavernous hemangiomas, have not been extensively documented. Methods: This case series retrospectively reviews six patients who developed hepatic hemangiomas following treatment with camrelizumab in combination with other chemotherapeutic agents. The series highlights the clinical course, imaging findings, management strategies, and outcomes associated with this complication. A detailed analysis was conducted to discern the potential causal relationship between camrelizumab therapy and the development of hepatic hemangiomas. Results: All six patients, after varying cycles of camrelizumab-based therapy, presented with hepatic lesions identified as cavernous hemangiomas on imaging. These findings were atypical for metastatic disease and were further complicated by significant clinical events, including massive intra-abdominal bleeding post-biopsy. Discontinuation of camrelizumab led to a reduction in the size of the hemangiomas in two cases, suggesting a potential link between the drug and the development of these vascular lesions. The incidence of RCCEP remained high, and the use of other agents such as bevacizumab did not mitigate the occurrence of hepatic hemangiomas, indicating a possible unique pathogenic mechanism associated with camrelizumab. Conclusion: Hepatic cavernous hemangioma may represent a rare but clinically significant irAE associated with camrelizumab therapy. This series underscores the importance of vigilant monitoring and a high index of suspicion for atypical hepatic lesions in patients undergoing treatment with PD-1 inhibitors. Further studies are warranted to elucidate the pathophysiology of this complication and to establish guidelines for the management and surveillance of patients receiving camrelizumab.